MULTILINGUALISM IN PRACTICE: LANGUAGE CHOICE AND CODE-SWITCHING AMONG UNIVERSITY STUDENTS IN WEST ACEH - Arafanianda, Sri; Juliana, Rena; Husna, Faizatul (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Multilingualism is a defining feature of higher education in West Aceh, where students navigate complex linguistic environments across academic and social domains. Understanding how these students manage language choice and code-switching offers insight into the dynamics of communication in multilingual contexts. This study aims to examine the code-switching practices and language preferences of multilingual students in a university setting. Employing a qualitative case study design, data were gathered from five English department students through semi-structured interviews and classroom observations. Thematic analysis was used to identify patterns in language behavior across different contexts. The analysis revealed that tag switching, particularly the insertion of Bahasa Indonesia phrases into English discourse, was the most frequent code-switching strategy during classroom interactions. Outside the classroom, Acehnese was predominantly used in domestic settings, while Bahasa Indonesia and English were commonly used in peer communication. Participants indicated that lecturers' use of code-switching between English and Bahasa Indonesia facilitated comprehension of complex academic content. These findings underscore the strategic and context-dependent use of multiple languages among students, reflecting the dynamic and adaptive nature of multilingual practices in West Aceh's higher education landscape.